PILKADA SERENTAK DAN HUKUM POLITIK: KONTROVERSI KEBIJAKAN PEMERINTAH PUSAT TERKAIT PUTUSAN HUKUM PILKADA KABUPATEN, SIMALUNGUN SUMATERA UTARA TAHUN 2015 - Ian Pasaribu (Politika: Jurnal Ilmu Politik, 2017)
This study examines, analyzes dna discusses Simultaneous elections Politics and Law: controversy Central Government Policies Related Legal Decisions Election District, North Sumatra Simalungun Where the Year 2015. On December 9, 2015 ago in elections Simalungun which is one of five areas was postponed due Regent Amran deputy candidate Sinaga experienced legal permaslahan. This study uses the theory of Elections, the concept of democracy and the electoral law. This study used qualitative methods with qualitative descriptive analysis techniques. The results of this study are Chronologically elections Simalungun, Inconsistency Regulations, Budget Swelling elections, Process Inaugural JR Saragih. Where the conclusions of this research local elections December 9, 2015 simultaneously experiencing the same problem as well as a substantial permasalahn. Registration problems associated pair of candidates is the responsibility of political parties to avoid any single candidate. On the issue of the availability of budget, the government and local governments need to give a strong political will to urgently solve the problem.